PREDICTORS OF MORTALITY AND POOR FUNCTIONAL OUTCOME IN PATIENTS WITH ACUTE STROKE ADMITTED TO A TERTIARY CARE HOSPITAL IN PAKISTAN - HAQ, MIU; KHAN, H; ASLAM, MT; AHMED, I; REHMAN, FU; IQBAL, N; KASHIF, M (Biological and Clinical Sciences Research Journal, 2024)
Stroke has a substantial impact on healthcare systems globally and is a leading cause of death and disability. The number of stroke cases in Pakistan is increasing, which makes it necessary to learn more about the factors that affect acute stroke patients' outcomes, especially in tertiary care settings. Objective: The study sought to determine socio-cultural causes linked to poor functional outcomes and death in acute stroke patients admitted to a tertiary care hospital in Pakistan, as well as to evaluate clinical variables, analyse pre-hospital effects, and identify demographic characteristics. Methods: The research was a retrospective cohort study at the Hayatabad Medical Complex in Peshawar, Pakistan, well-known for its state-of-the-art stroke treatment facilities. A sample size of 346 acute stroke patients hospitalised between January 2021 and December 2022 was selected to achieve statistical power. Adult patients with acute stroke diagnoses met the inclusion criteria, and strict exclusion standards guaranteed data uniformity and correctness. Descriptive statistics and logistic regression were used to assess pre-hospital, clinical, and demographic data obtained from electronic medical records. Results: On average, the patients were 65.2 years old, and 54.91% were male. The prevalence of ischaemic strokes was 72.83% higher than that of hemorrhagic strokes. Age (OR: 1.08, p < 0.001), stroke severity (OR: 1.42, p < 0.001), diabetes mellitus (OR: 2.10, p = 0.005), delayed medical treatment (OR: 1.89, p = 0.010), and inadequate family support (OR: 2.45, p = 0.003) were significant predictors of death. Age (OR: 1.12, p < 0.001), stroke severity (OR: 1.58, p < 0.001), cardiovascular disease (OR: 1.87, p = 0.044), delaying seeking medical assistance (OR: 1.96, p = 0.005), and health-seeking behaviour (OR: 2.18, p = 0.002) were among the factors that predicted poor functional outcomes. Conclusion: Our research highlights the significance of prompt care, social support, and rehabilitation in improving the prognosis of individuals with acute stroke in Pakistan.